2018
DOI: 10.26515/rzsi/v118/i2/2018/121437
|View full text |Cite
|
Sign up to set email alerts
|

First photographic evidence of Asian Golden Cat <i>Catopuma temminckii</i> (Vigors and Horsfield, 1827) from Neora valley National Park, Central Himalayas, India

Abstract: Despite of the knowledge gap on estimated population and density of this species across its geographical range, Asian Golden Cat is currently listed as Near Threatened in the IUCN Red List and listed in Appendix I by CITES as the current population is dwindling (McCarthy et al., 2015;Dhendup, 2016). It is also included under the Scheduled I in the Wildlife (Protection) Act, 1972 (Anonymous, 1972. Asian Golden Cat is a poorly studied species both in wild and captivity. Much of the information on various ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The golden morph was reported to be the most widely distributed form (Jigme, 2011;Dhendup, 2016;Nijhawan et al, 2019). A similar observation was also made from the northeast state (West Bengal, Assam, Mizoram, Nagaland, and Tripura) of India (Gouda et al, 2016;Chatterjee et al, 2018) and Nepal (Ghimirey and Pal, 2009). Our findings also corroborate with these observations as the golden morph was photographed from relatively wider elevation boundaries than the other co-occurring morphs.…”
Section: Altitudinal Distributionmentioning
confidence: 62%
See 1 more Smart Citation
“…The golden morph was reported to be the most widely distributed form (Jigme, 2011;Dhendup, 2016;Nijhawan et al, 2019). A similar observation was also made from the northeast state (West Bengal, Assam, Mizoram, Nagaland, and Tripura) of India (Gouda et al, 2016;Chatterjee et al, 2018) and Nepal (Ghimirey and Pal, 2009). Our findings also corroborate with these observations as the golden morph was photographed from relatively wider elevation boundaries than the other co-occurring morphs.…”
Section: Altitudinal Distributionmentioning
confidence: 62%
“…Asiatic golden cat, Captopuma temminckii Vigors and Horsfield, 1827, is a medium sized elusive and the largest group of smaller oriental felines (Bashir et al, 2011;Gouda et al, 2016;Ghose et al, 2019). The golden cat has been categorized as Near Threatened on the IUCN Red List of Threatened Species (Dhendup, 2016;Wangyel et al, 2020) and is listed in Appendix I of CITES (McCarthy et al, 2015;Chatterjee et al, 2018) and Schedule I of the Forest and Nature Conservation Act of Bhutan, 1995(FNCA, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…The colonization of granivorous in cropland and wasteland because the open habitats provide abundant seed grain (Chettri et al, 2005; Diaz and Telleria, 1996). Fruiting plants are regulated by the frugivorous birds (Chatterjee et al, 2018; Trager and Mistry, 2003). We observed that the abundance of frugivorous birds is higher in forest areas than in residential areas because of high fruit plant diversity (Gomes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of tigers, co-predators and prey has been recommended in the upper Himalayan region (e.g. Bhattacharya & Habib, 2016; Adhikarimayum & Gopi, 2018; GTF, 2019; Chatterjee et al, 2020). Several studies have reported that tigers move across country borders in the Terai Arc Landscape and Himalayas (e.g.…”
Section: Synthesis and Interpretationmentioning
confidence: 99%